2017
DOI: 10.1080/00102202.2017.1297807
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ce/Zr Ratio on the Synergistic Effect over CuCe1–xZrxOy/ZSM-5 Catalysts for the Self-Sustained Combustion of Carbon Monoxide

Abstract: The self-sustained combustion of CO was studied over a series of CuCe 1-x Zr x O y /ZSM-5 catalysts with different Ce/Zr molar ratios to evaluate the correlation of their structural characteristics with catalytic performance. The obtained results demonstrated that the activity of the cerium-containing catalysts was much higher than that of the CuZr 1 /Z, with the activity of CO combustion following the order: CuZr 1 /Z < CuCe 0.25 Zr 0.75 /Z < CuCe 0.5 Zr 0.5 /Z < CuCe 1 /Z < CuCe 0.75 Zr 0.25 Z. After cerium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Cu(NO 3 ) 2 ·3H 2 O, Ce(NO 3 ) 3 ·6H 2 O and Zr(NO 3 ) 4 ·5H 2 O were combined in a 4:3:1 M ratio and dissolved fully in 70 mL of ethanol at 80°C. This Cu:Ce:Zr ratio was selected on the basis of our previous study according to its good redox capability and oxygen storage capacity for CO oxidation [22,23]. Then, 0.24 mol/L of an oxalic acid solution was used as a pore former and was added quickly to the aforementioned nitrate solution with stirring to evaporate ethanol and to fully dissolve until a gel was formed at 80°C over nearly 6 h. After aging at room temperature for approximately 48 h, the gel was dried at 105°C for 12 h and then calcined in air at 550°C for 2 h.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Cu(NO 3 ) 2 ·3H 2 O, Ce(NO 3 ) 3 ·6H 2 O and Zr(NO 3 ) 4 ·5H 2 O were combined in a 4:3:1 M ratio and dissolved fully in 70 mL of ethanol at 80°C. This Cu:Ce:Zr ratio was selected on the basis of our previous study according to its good redox capability and oxygen storage capacity for CO oxidation [22,23]. Then, 0.24 mol/L of an oxalic acid solution was used as a pore former and was added quickly to the aforementioned nitrate solution with stirring to evaporate ethanol and to fully dissolve until a gel was formed at 80°C over nearly 6 h. After aging at room temperature for approximately 48 h, the gel was dried at 105°C for 12 h and then calcined in air at 550°C for 2 h.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…This molar ratio was determined based on our previous study where we found that this ratio can form a M-cerium synergy and a cerium-zirconium solid solution, which improved the redox capability and oxygen storage capacity of the catalysts. 28 The resulting solution was stirred at 80 °C with a pH of ∼7.0 for 24 h. Subsequently, the samples were dried and then calcined at 550 °C for 4 h, pressed and sieved to 20–40 mesh. The chemical composition of the catalysts was measured by inductively coupled plasma-atomic emission spectroscopy (ICP-AES) to confirm the M/Ce/Zr molar ratio of the catalysts.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneous oxidation of CO and CH 4 on Pt/Al 2 O 3 and Pt/CeO 2 results in a reverse hysteresis for methane oxidation [5]. Moreover, CO self-sustained combustion over the Cu-Ce/ZSM-5 or CuCe 1-x Zr x O y /ZSM-5 catalyst has been reported [91,92]. The explanation of hysteresis effects by multiple steady states has been comprehensively reviewed by Hlaváček et al [93].…”
Section: Origin Of Hysteresis Phenomenon In Low-temperature Co Oxidationmentioning
confidence: 99%
“…Increasing CO concentration in inlet gas causes a higher light-off temperature or ignition point, the hysteresis loop increases upon increasing the CO concentrations [52,56,74,77,87,126,142] Inlet Temperature Ignition and extinction shifted to higher temperatures with rapid increase in CO conversion [77,[128][129][130][131][132][133][134] Surface Contamination and Aging Increase in the hysteresis width due to the removal of contamination that blocks active sites [75,94,141] [55, 94,140] Rate of temperature ramp-up Increase in the temperature ramp-up result in shifting the ignition curve to higher temperatures [72,92] Inhibition parameters Different inhibiting species accumulation on catalyst surface can change the shape of hysteresis curves and increase the width of the hysteresis. [141,142].…”
Section: Parameter Effect On Hysteresis Curve Referencementioning
confidence: 99%